PEDRO FLORES EN PRAGA, EN 1946 - Stepanek, Pavel (Imafronte, 1986)
This paper concerns the presence of the Murcian peinter Pedro Flores in Czecho-Slovakia together with the group of Spanish painters of the School of Paris. at the end of the Second World War, in order to holdin 1946 an exhibition, called Art in Republican Spain. The celebration of this display was possible because of the sympathy that country showed the republican cause, which definitely gave rise to a lively cultural interchange supported by the, prosperous Spanish-Czechoslovak relationship. As a result of this ultrnospherr there appeared a whole artistic literature based on Spanish themes. the 1946 exhibition (Pedro Flores’ work of which is stressed) was joyfully greeted because, it served as a interesting point for a number íf activy artists exiled from their native country, and on account of the interest the collection of their work offered as an example of the artistic vanguard and the special capture of French atmosphere and influence. The basic nucleus of this paper focuses on the figure of the Murcian Pedro Flores and on the reproduction of his paintings kept in Prague. The description of his appearence and Spanish ways. made by the critics, are fundamental data for understanding an aspect, which has been quite forgotten, of his paintings.